Assessment of alcohol consumption in liver transplant candidates and recipients: The best combination of the tools available. Issue 7 (26th May 2014) - Piano, Salvatore; Marchioro, Lucio; Gola, Elisabetta; Rosi, Silvia; Morando, Filippo; Cavallin, Marta; Sticca, Antonietta; Fasolato, Silvano; Forza, Giovanni; Chiara Frigo, Anna; Plebani, Mario; Zanus, Giacomo; et al.
<x xml:space="preserve">Abstract</x> The detection of alcohol consumption in liver transplant candidates (LTCs) and liver transplant recipients (LTRs) is required to enable a proper assessment of transplant eligibility and early management of alcohol relapse, respectively. In this clinical setting, urinary ethyl glucuronide (uEtG), the Alcohol Use Disorders Identification Test for Alcohol Consumption (AUDIT‐c), serum ethanol, urinary ethanol, carbohydrate‐deficient transferrin (CDT), and other indirect markers of alcohol consumption were evaluated and compared prospectively in 121 LTCs and LTRs. Alcohol consumption was diagnosed when AUDIT‐c results were positive or it was confirmed by a patient's history in response to abnormal results. Alcohol consumption was found in 30.6% of the patients. uEtG was found to be the strongest marker of alcohol consumption (odds ratio = 414.5, P < 0.001) and provided a more accurate prediction rate of alcohol consumption [area under receiving operating characteristic (ROC) curve = 0.94] than CDT (area under ROC curve = 0.63, P < 0.001) and AUDIT‐c (area under ROC curve = 0.73, P < 0.001). The combination of uEtG and AUDIT‐c showed higher accuracy in detecting alcohol consumption in comparison with the combination of CDT and AUDIT‐c (area under ROC curve = 0.98 versus 0.80, P < 0.001). Furthermore, uEtG was the most useful marker for detecting alcohol consumption in patients with negative AUDIT‐c results. In conclusion, the combination of AUDIT‐c and uEtG improves the detection of alcohol consumption in LTCs and LTRs. Therefore, they should be used routinely for these patients. Liver Transpl 20:815–822, 2014. © 2014 AASLD.